Penerapan Etika dan Budaya di Lingkunga Sekolah Dasar untuk Siswa dan Siswi Kelas 6 SDN 05 Air Tawar - Novalia indra; Recy Harviani Zurwanty; Pinta Medina (LPPM Universitas Dharma Andalas, 2023)
Community Service (PKM) is a form of the Tridharma of Higher Education. This PKM is proposed to carry out socialization and educational activities in one of the elementary schools in the city of Padang, West Sumatra. This activity is proposed to socialize the Application of Ethics and Learning Culture in the Elementary School Environment for Grade 6 Students of SD N 05 Air Tawar. Therefore we focus on carrying out this activity for grade 6 students at Sdn 05 Air Tawar, so that grade 6 students at Sdn 05 Air Tawar can apply ethics and culture properly later. after the implementation of the PKM that we did at the school that the father or mother led.